Diagnóstico sobre la aplicación de metodologías ágiles para la gestión de proyectos de construcción en Colombia (2022)
The present work aims to describe how construction projects can benefit from the use of agile methods, as a tool for construction project management. As time progresses, the way of managing projects evolves, as well as the way in which the projects of different companies are managed, as well as in the construction sector. In this way, demand and innovation are necessary to optimize the resources of each plan available, and efficiently meet the objectives planned at the beginning of each project. Becerra (2021), states that: Construction projects, among other things, offer us the possibility of reliably calculating the economic value of the country's resources. These activities offer opportunities to improve the planning and manageme nt of such projects. As best practices, some construction companies develop improvement projects according to the Project Management Institute (PMI) methodology, but as projects evolve, they become more complex at the time of development, construction comp anies vary in the ways to execute them. projects, Integrating methods and software to improve development management for the activities that arise in construction projects, including: plan; Oath, Six Sigma, etc. (p.24). In this case, the research focuses on agile methodologies for the management and planning of construction projects, giving the approach that revolutionizes the way of working on projects, the adaptation of construction companies and the management of processes in construction projects.